The study of the relation between requirement engineering techniques and challenges in software industry - Besrour, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Requirement engineering (RE) filed has been intensively studied by researchers in order to reduce its challenges effects. By one estimate requirement engineering errors costs 10 times more than coding errors, which reflect that the earlier errors has been discovered the better. This paper aims to study the relation between RE techniques and challenges. Moreover a conceptual research framework has been propose to link aforementioned research items. Consequently a research survey has been identified and distributed to 246 software engineering respondents in order to assess proposed framework. Note that this paper is going to highlight hypothesis testing details and obtained results. Â© 2015 IEEE.